Trehalose-6-phosphate and SnRK1 kinases in plant development and signaling: the emerging picture - Gazzarrini, Sonia; Tsai, Allen Yi-Lun (Frontiers in Plant Science, 2014)
Carbohydrates, or sugars, regulate various aspects of plant growth through modulation of cell division and expansion. Besides playing essential roles as sources of energy for growth and as structural components of cells, carbohydrates also regulate the timing of expression of developmental programs. The disaccharide trehalose is used as an energy source, as a storage and transport molecule for glucose, and as a stress-responsive compound important for cellular protection during stress in all kingdoms. Trehalose, however, is found in very low amounts in most plants, pointing to a signaling over metabolic role for this non-reducing disaccharide. In the last decade, trehalose-6-phosphate (T6P), an intermediate in trehalose metabolism, has been shown to regulate embryonic and vegetative development, flowering time, meristem determinacy and cell fate specification in plants. T6P acts as a global regulator of metabolism and transcription promoting plant growth and triggering developmental phase transitions in response to sugar availability. Among the T6P targets are members of the Sucrose-non-fermenting1-Related Kinase1 (SnRK1) family, which are sensors of energy availability and inhibit plant growth and development during metabolic stress to maintain energy homeostasis. In this review, we will discuss the opposite roles of the sugar metabolite T6P and the SnRK1 kinases in the regulation of developmental phase transitions in response to carbohydrate levels. We will focus on how these two global regulators of metabolic processes integrate environmental cues and interact with hormonal signaling pathways to modulate plant development.